PERSOALAN HUKUM NELAYAN DAN KELOMPOK NELAYAN DI KABUPATEN TAKALAR - Abd. Asis; Slamet Sampurno; Amir Ilyas; Dara Indrawati; Audyna Mayasari Muin; Kadarudin (Sekolah Tinggi Ilmu Hukum Awang Long, 2018)
Geographically, Takalar Regency is mostly surrounded by the ocean and also borders the Makassar Strait, although geographically it is not the same as other regencies such as those in South Sulawesi (for example Selayar Islands Regency) but according to BPS Takalar Regency that sectors that have contributed Takalar's economy is very large, it is still in the agricultural sector, which is 49.94 percent, with the fisheries sub-sector contributing around 36.73 percent, thus the Regional Government of Takalar Regency should pay more attention to the lives of fishermen so that the fishermen do not change professions to jobs that on land.